Proving triptycene homoconjugation with the same chromophore but different connectivity to the core [data] - Elbert, Sven; Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
Homoconjugation is a phenomenon discussed for various π-systems where classical conjugation is broken by e.g. methylene units but still a stabiliza...